Indonesia's Sustainable Fisheries Agenda: From Policy to Practice of Indonesian National Plan of Action - Apriliana, Adhitya Nini Rizki (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. There are still unanswered questions regarding illegal fishing practices in Indonesia that pose a significant threat to biodiversity and contribute to the overexploitation of fisheries resources. Purpose. Not only grappling with the imbalance between abundant fishing potential, this practice essentially includes a range of other offenses beyond the act of stealing fish. Method. To address these pressing challenges, Indonesia has taken steps to optimize its national marine and fisheries resources. As a member of RPOA-IUU in 2007, it was immediately brought to the attention of this archipelagic nation of more than 17,000 islands in Southeast Asia to develop a National Action Plan (NAP) as a means to combat illegal fishing practices in Indonesian waters. Results. After being implemented for almost a decade, illegal fishing practices continue to occur. This socio-legal research questions the effectiveness of Indonesia's National Action Plan in combating illegal fishing. Through a combination of statutory and conceptual approaches, this research analyzes how this national instrument aligns with the Fisheries Legislation Model to address illegal fishing at the national level. Conclusion. It finds that this phenomenon is supported by the lack of essentials in fishing activities such as engine fuel, fishing gear, boat engines, supplies, and logistics that are still difficult for fishers to access. Similarly